DYNAMICS OF FOREIGN ECONOMIC RELATIONS OF THE KHIVA KHANATE - Muborak Matyakubova Madrimovna (Scholar Express Journal, 2025)
The Khiva Khanate, as one of the important political and economic centers of the East, actively established international and regional trade relations in the 16th-19th centuries. The geostrategic location of the Khanate, bordering Iran, Afghanistan, Russia, the Kazakh steppes and other territories inhabited by Turkic peoples, created favorable conditions for foreign trade. Merchants from different countries, in addition to visiting the Khorezm markets for commercial purposes, also used the Khiva Khanate as a transit area. In particular, sources indicate that the route through which Russian, Kazakh, Turkmen and Bukhara merchants communicated with each other passed through the territory of the Khiva Khanate.
Keywords: Khiva Khanate; transit area; regional trade